INFLUENCE OF THE TIME OF DISINHIBITION TO TRANSIENTS AND WEAR OF THE FRICTION LININGS IN AN ASYNCHRONOUS MOTOR - V. V. Solencov; V. V. Brel (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Time and the stopping distance of the electric drive with frequent starting-and-braking modes that contain embedded asynchronous motor with a recessed combined braking device depend on the moment of an electromagnet disinhibition. At the same time other important criteria are taken into the account, i.e. wear resistance of the brake device and the smoothness of the deceleration of the electric drive. In general such an asynchronous motor contains asynchronous engine with squirrel-cage rotor, electromechanical normally-closed brake, electromagnetical slip clutch and control circuit. The mechanical characteristics of the deceleration of asynchronous motor with recessed combined brake device at different moments of an electromagnet disinhibition are presented. The mathematical model is featured and the transients in such a motor are presented. Formation models for computer research were carried out in the Fortran 2008 programming language. Calculation of the system of differential equations was fulfilled by the Runge – Kutta method. The deceleration of the electromechanical brake at various speeds caused different time values and stopping distances. The plots of stopping distance and the braking time at various moments of an electromagnet disinhibition are demonstrated. The optimum moment of switching on an electromechanical brake, providing small stopping distance and the braking time is the time when the speed wвкл = 0,6–0,8 of the nominal. In this case the acceptable number of brake applications for friction linings (compared with mechanical braking) will increase by 1.6–2.8 times. The pilot study confirmed the validity of the obtained mathematical models and discovered patterns.